Vibration Analysis of Emco Maximat V13 Lathes due to Variations in Machine Rotation and Feeding Depth On the Flat Lathe Process of ST 42 Steel - Saut Samuel Putra Sibarani; Arvian enggal putra; Yosua luis vigo sitompus; Hengki tornado (Universitas Riau Kepulauan, 2025)
The purpose of this study is to analyze the vibration behavior of the EMCO Maximat V13 lathe due to variations in machine rotation and variations in cutting depth. This research is an experimental research. The research specimens amounted to 45 specimens. The data of this study was obtained from the measurement of vibration deviation using Vibscaner which was measured on the toll post of the lathe. From the data, it can be analyzed that the effect of increasing the rotation of the machine will cause an increase in the vibration of the lathe marked by an increase in the measured deviation on the Vibscaner, as well as the result of cutting, together both the increase in rotation and the increase in feeding together affect the increase in the vibration of the lathe measured on the Vibscaner. The test uses quantitative statistics. The results of the hypothesis test showed: (1) There is an effect of cutting speed on the vibration of the lathe, this can be seen from the significance value (sig) 0.000 < 0.05 and the calculation of 8.882 > 2.062 ttables. (2) There is an effect of cutting depth on the vibration of the lathe, this can be seen from the significance value (sig) of 0.000 < 0.05 and the tcount of 5.652> 2.063 ttables, and (3) There is an effect of cutting speed and cutting depth together on the vibration of the lathe, this can be seen from the significance value (sig) 0.000 < 0.05 and tcount 11.734 > 2.062 table.